SYSTEM OF PREVENTIVE АCTION OF CONSTRUCTION ENTERPRISES ON THE BASIS OF IDENTIFICATION OF ANTICRISIS POTENTIAL - O. Bielienkova (Astana IT University, 2020)
Peculiarities of formation of anti-crisis potential of construction enterprises are considered. Construction companies are rapidly adapting to the requirements of the digital economy, transforming the management structure, business processes. To improve the system of preventive protection and protection of enterprises from loss of viability and subsequent self-liquidation or bankruptcy, a system of indicators is proposed, which allows to identify existing risks and threats at an early stage. In order to improve the mechanism of control of the stability of the system of anti-crisis potential of construction enterprises in the medium term, a cluster analysis was performed. The study was based on 53 enterprises of the type of activity «construction». This study allowed us to identify the most important, priority, leading indicators of the loss of economic security and to clarify the threshold values of these indicators and the degree of their «blurring» in the unstable conditions of the external economic environment. Indicators of crisis state of construction enterprises are determined by means of fuzzy sets, among which it is possible to allocate: level of capital consumption by owners, level of operating sales on retained earnings, return on working capital on retained earnings, cost of operating expenses on personnel costs, term of accounts payable. The main direct and indirect signs of deterioration of the anti-crisis potential of the enterprise are revealed. The model of information interaction of divisions of the enterprise is offered. All processes of information exchange with the help of IMS (Information Management System) have the ultimate goal of the maximum possible exclusion from the business practice of paper documents and the transition to direct paperless data exchange (in the practice of construction is an example of creating a BIM-model of objects).